Un « Deep / dark web » ? Les métaphores de la profondeur et de l’ombre sur le réseau Tor - Jean-François Perrat (Netcom)
Tor (The Onion Router) is a subnetwork of the Internet which makes it possible for mere users and contents providers to conceal their identity on special websites called location-hidden services. Based on the analysis of the technical documentation, the common representations and field-material from the location-hidden services, this article evaluates the relevance of the « deep web » and « dark web » metaphors often used to talk about the location-hidden services of Tor. It suggests to rather use the term « .onion web ».